2021
DOI: 10.3390/coatings11060707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CeO2 on Corrosion Resistance of High-Current Pulsed Electron Beam Treated Pressureless Sintering Al-20SiC Composites

Abstract: In this paper, the effect of rare earth Ce on the corrosion resistance of Al-20SiC composites treated with high-current pulsed electron beams is investigated, and the corresponding corrosion mechanism is proposed. The scanning electron microscope (SEM) results show that cracks arise on the surface of Al-20SiC composites prepared by pressureless sintering. After electron beam treatment, the pores on the surface are reduced because of the filling of Al liquid. After adding CeO2 to Al-20SiC composites, the wettab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Meantime, it can be observed that a certain amount of pore structure was distributed in the vicinity of the titanium carbide particles. Studies [25] have shown that when the sintering temperature is 590 • C, the liquid Al has a high viscosity, which leads to a relatively poor fluidity of liquid aluminum, making the material unable to complete its feeding during solidification and, finally, forming a pore structure. After HCPEB treatment, the surface morphology of Al-20TiC was changed, and it can be clearly seen that the large pores on the surface of the Al-20TiC were significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Meantime, it can be observed that a certain amount of pore structure was distributed in the vicinity of the titanium carbide particles. Studies [25] have shown that when the sintering temperature is 590 • C, the liquid Al has a high viscosity, which leads to a relatively poor fluidity of liquid aluminum, making the material unable to complete its feeding during solidification and, finally, forming a pore structure. After HCPEB treatment, the surface morphology of Al-20TiC was changed, and it can be clearly seen that the large pores on the surface of the Al-20TiC were significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…The current density of DC electroplating is much lower than the peak current density of pulse electroplating. Pulse electrodeposition not only has an effect on the morphology of the plated layer, but also on the corrosion resistance of the plated coating [23][24][25][26][27][28]. However, the mechanism of the effects of pulse electroplating parameters on the morphology and corrosion resistance of silver coatings have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, this preparation method produces significant casting defects, such as porosity, cracking, and agglomeration, which limit the wide application of Al-20SiC composites [ 10 ]. Therefore, it is necessary to improve the properties of Al-20SiC composites using different treatment methods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%